2014
DOI: 10.14430/arctic4402
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Agriculture for Alaska and the Circumpolar North: Part I. Development and Status of Northern Agriculture and Food Security

Abstract: ABSTRACT. Alaska is food insecure, importing the vast majority of its agricultural products and commodities and maintaining a minimal year-round food supply. Much of the circumpolar North, with some notable exceptions, is also food insecure and similarly reliant on foods imported from outside regions. The stark differences in food policies, food security, and overall production that exist between individual countries and regions of the circumpolar North are likely due to variability in their physical and socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 42 publications
0
23
0
1
Order By: Relevance
“…Paragi et al (2010) reported that from 2001 to 2005, less than 1% of red meat produced in Alaska came from reindeer. The history and present status of reindeer herding in Alaska has been discussed previously, in detail (Stevenson et al, 2014a).…”
Section: Challenges In Raising Livestock and Poultry At High Latitudesmentioning
confidence: 99%
See 4 more Smart Citations
“…Paragi et al (2010) reported that from 2001 to 2005, less than 1% of red meat produced in Alaska came from reindeer. The history and present status of reindeer herding in Alaska has been discussed previously, in detail (Stevenson et al, 2014a).…”
Section: Challenges In Raising Livestock and Poultry At High Latitudesmentioning
confidence: 99%
“…Very little of Alaska's food demand is met by local agriculture, and its year-round food supply is insufficient (Alaska State Senate, 1976;Drew, 1977;UAF CES, 2006;Consenstein, 2010;Helfferich, 2010;Helfferich and Tarnai, 2010;Stevenson et al, 2014a). Its communities are supported by some local farming and gardening ( Fig.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations